2010
DOI: 10.3138/jvme.37.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Veterinary Obstetrics Using Three-Dimensional Animation Technology

Abstract: In this three-year study, test scores for students taught veterinary obstetrics in a classroom setting with either traditional media (photographs, text, and two-dimensional graphical presentations) were compared with those for students taught by incorporating three-dimensional (3D) media (linear animations and interactive QuickTime Virtual Reality models) into the classroom lectures. Incorporation of the 3D animations and interactive models significantly increased students' scores on essay questions designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 2 publications
2
13
0
1
Order By: Relevance
“…The GIF showed that understanding the implications of the position of the foal in relation to the pelvis was vital. The results of the present study were consistent with earlier reports that suggested that increased use of computer‐aided tools was well received by students, associated with improved learning, and conveyed improved understanding of spatial relation between the calf and pelvis 4…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The GIF showed that understanding the implications of the position of the foal in relation to the pelvis was vital. The results of the present study were consistent with earlier reports that suggested that increased use of computer‐aided tools was well received by students, associated with improved learning, and conveyed improved understanding of spatial relation between the calf and pelvis 4…”
Section: Discussionsupporting
confidence: 91%
“…Historically, the teaching of veterinary obstetrics has been limited to descriptions of birth and dystocia through the use of photographs, text and two‐dimensional graphical representations 4 5. Clinical skills models are also utilised in obstetrics teaching, and hands‐on practical experiences in a clinical setting can sometimes be provided to supplement learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When technical guidelines were well understood and applied to the property, these could result not only in higher production (23) but in improved animal welfare (34) . The process of learning about new technologies (35) , besides the understanding of productivity and extension services (36) contribute to the management and development of more productive systems. Policies for the development of human capital (37) were important actions for economic and social development and consequently production (38) .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the University of Georgia developed a software program called ''The Glass Horse''. 7 This software allows virtual visualizing the equine digestive tract in a three-dimensional, interactive manner. This software has been positively received by students and has facilitated learning of a complicated gastrointestinal organ system, and although it is limited by single species and organ system, it is a step in the right direction.…”
Section: Introductionmentioning
confidence: 99%